Technical analysis: trading profitably with Elliott Wave Theory - Liu, Chang. (2011)
The Elliott Wave Principle is a form of technical analysis that traders use to analyze financial market cycles and forecast market trends. The Wave Theory was first proposed by Ralph Nelson Elliott, an accountant, in the 1930s. He observed and identified repetitive patterns in the stock market and in nature. He believed all human activities were influenced by these identifiable wave series, from pessimism to optimism and back in a natural sequence.